Global Existence Results for Functional Differential Inclusions with State-Dependent Delay - Benchohra, Mouffak; Henderson, Johnny; Medjadj, Imene (Mathematical Modelling and Analysis, 2014)
Our aim in this work is to study the existence of solutions of a functional differential inclusion with state-dependent delay. We use the Bohnenblust–Karlin fixed point theorem for the existence of solutions.